Accountability and Internal Control of Religious Organizations (Study on GKPB Immanuel Tabanan) - Helena Maharina Nalle; Ni Luh Putu Sri Purnama Pradnyani; Putu Aristya Adi Wasita (Pertapsi-Indonesia collaborated with Petra Christian University, 2023)
Religious organizations require accountability practices in managing their funds. These accountability practices are reinforced through the implementation of internal controls. The discovery of fraud in religious organizations shows that their internal controls are weak and their management lacks accountability. This research focuses on GKPB Immanuel Tabanan, aiming to understand the implementation of accountability and internal controls in managing acquired funds. The method used in this research is a descriptive qualitative approach, involving the collection of primary data through in-depth interviews, observations, and documentation. Data validity is tested using triangulation techniques. The research shows that accountability at GKPB Immanuel Tabanan has been effective. This is evident from the assignment of tasks and responsibilities to the church administrators, clear procedures in the selection of church administrators, and the church treasurer's role in overseeing all cash expenditures. Furthermore, the church has also implemented a code of ethics. The implementation of the internal control system has been effective. Procedures for cash receipts and disbursements have been established. Steps to mitigate risks are in place. Each cash expenditure requires authorization from the relevant authorities. Information regarding the church's financial reports is presented openly and accessible to the congregation, and internal audits are being conducted. the church has also implemented a code of ethics. The implementation of the internal control system has been effective. Procedures for cash receipts and disbursements have been established. Steps to mitigate risks are in place. Each cash expenditure requires authorization from the relevant authorities. Information regarding the church's financial reports is presented openly and accessible to the congregation, and internal audits are being conducted. the church has also implemented a code of ethics. The implementation of the internal control system has been effective. Procedures for cash receipts and disbursements have been established. Steps to mitigate risks are in place. Each cash expenditure requires authorization from the relevant authorities. Information regarding the church's financial reports is presented openly and accessible to the congregation, and internal audits are being conducted